2003
DOI: 10.1002/anie.200351175
|View full text |Cite
|
Sign up to set email alerts
|

Biomineral‐Silica‐Induced Zeolitization of Equisetum Arvense

Abstract: The performance of bulk materials often depends on the size and habit of the primary particles, and their ordering into hierarchical structures. In the area of catalysis and separation processes, ordered materials with well-defined periodic structures and controlled sizes are highly desired. Hierarchical porous structures combine the benefits of each pore-size regime and are expected to lead to higher efficiency and new applications in catalytic and separation processes, biomolecular separations, and chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 15 publications
0
56
0
Order By: Relevance
“…Hierarchical structuring of zeolitic materials is a burgeoning area of scientifi c interest due to its potential technological impact in adsorption/separation, catalysis, microelectronic, biomolecular separation and chromatographic applications, [1][2][3] as it combines characteristics of pore size regimes with many different length scales. Materials with combinations of micro-/ mesopores, [ 4 ] micro-/macropores, [ 5 ] meso-/macropores [ 6 ] or porosity spreading up to the three orders [ 7 ] were synthesized by employing two different approaches: a) Template-directed synthesis that utilizes the inherent porosity of temporary/sacrifi cial templates (artifi cial or biological) to form hierarchical porous inorganic frameworks by an imprinting process or an extraction process [ 7 , 8 ] and b) the synthesis of hierarchical porous composites by in situ or ex situ coatings of microporous and mesoporous inorganic frameworks onto very open (macro-, mega) porous substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical structuring of zeolitic materials is a burgeoning area of scientifi c interest due to its potential technological impact in adsorption/separation, catalysis, microelectronic, biomolecular separation and chromatographic applications, [1][2][3] as it combines characteristics of pore size regimes with many different length scales. Materials with combinations of micro-/ mesopores, [ 4 ] micro-/macropores, [ 5 ] meso-/macropores [ 6 ] or porosity spreading up to the three orders [ 7 ] were synthesized by employing two different approaches: a) Template-directed synthesis that utilizes the inherent porosity of temporary/sacrifi cial templates (artifi cial or biological) to form hierarchical porous inorganic frameworks by an imprinting process or an extraction process [ 7 , 8 ] and b) the synthesis of hierarchical porous composites by in situ or ex situ coatings of microporous and mesoporous inorganic frameworks onto very open (macro-, mega) porous substrates.…”
Section: Introductionmentioning
confidence: 99%
“…A seeded growth methodology was followed to create a hierarchical zeolitic tissue that mimics the initial cellular structure of wood. Valtchev et al used other vegetal (Equisetum arvense) as biological hard template to create hierarchical molecular sieves [145]. The authors reported the in-situ zeolitization of the vegetal macrotemplate by the biogenic silica present in the fresh plant, as the Equisetum arvense contains 13% wt of silica.…”
Section: Direct Synthesis Of Hierarchical Zeolites By Dual Templatingmentioning
confidence: 99%
“…They have many advantages compared to artificial ones due to their abundant, renewable, and environmentally friendly properties. They also have various structures, splendid morphologies, and good biocompatibilities [1,[15][16][17]. At present, all kinds of biological materials have been used as hard template such as plants: wood [18], bamboo [19], diatoms [20]; animal tissue: cuttlebone [21], echinus bone [22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%